Total error shift patterns for daily CT on rails image-guided radiotherapy to the prostate bed - Cavalieri, Ronaldo; Gay, Hiram A.; Liu, Jingxia; Ferreira, Maria Clara; Mota, Helvecio C.; Sibata, Claudio H.; Allison, Ron R. (My University, 2011)
Background To evaluate the daily total error shift patterns on post-prostatectomy patients undergoing image guided radiotherapy (IGRT) with a diagnostic quality computer tomography (CT) on rails system. Methods A total of 17 consecutive post-prostatectomy patients receiving adjuvant or salvage IMRT using CT-on-rails IGRT were analyzed. The prostate bed's daily total error shifts were evaluated for a total of 661 CT scans. Results In the right-left, cranial-caudal, and posterior-anterior directions, 11.5%, 9.2%, and 6.5% of the 661 scans required no position adjustments; 75.3%, 66.1%, and 56.8% required a shift of 1 - 5 mm; 11.5%, 20.9%, and 31.2% required a shift of 6 - 10 mm; and 1.7%, 3.8%, and 5.5% required a shift of more than 10 mm, respectively. There was evidence of correlation between the x and y, x and z, and y and z axes in 3, 3, and 3 of 17 patients, respectively. Univariate (ANOVA) analysis showed that the total error pattern was random in the x, y, and z axis for 10, 5, and 2 of 17 patients, respectively, and systematic for the rest. Multivariate (MANOVA) analysis showed that the (x,y), (x,z), (y,z), and (x, y, z) total error pattern was random in 5, 1, 1, and 1 of 17 patients, respectively, and systematic for the rest. Conclusions The overall daily total error shift pattern for these 17 patients simulated with an empty bladder, and treated with CT on rails IGRT was predominantly systematic. Despite this, the temporal vector trends showed complex behaviors and unpredictable changes in magnitude and direction. These findings highlight the importance of using daily IGRT in post-prostatectomy patients.
Keywords: Post-prostatectomy radiotherapy; IGRT; CT on rails; shift total error; prostate bed